Akad Bisnis dalam Platform Digital E-Commerce : Perspektif Kitab Fathul Qorib - Miftachul Ulum; Abdul Mun'im (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to analyze the suitability of e-commerce contract practices with the principles of classical Islamic jurisprudence as explained in the Fathul Qorib book. This study uses a qualitative-descriptive approach with a literature analysis method of classical Islamic jurisprudence sources and modern digital business practices. The results of the study indicate that conceptually, e-commerce contracts fulfill the main elements of Islamic contracts such as ijab and qabul, clarity of the transaction object (ma'qud 'alaih), and the element of willingness (taradhi) between the two parties. The Fathul Qorib book emphasizes that the validity of a contract does not depend on the form of the medium, but rather on the fulfillment of its conditions and pillars. Thus, contracts through digital media can be considered valid if these elements are met.